Environmental and endogenous influences on carbohydrate assimilation and allocation of apple trees (Malus domestica Borkh) - Pretorius, Jeremia Jesaja Bierman (Stellenbosch : Stellenbosch University, 2012)
Stellenbosch University. Faculty of AgriSciences. Dept. of Horticulture.